67.7k views
3 votes
What is the distance between (-5, 3) and (7, 3)? Explain using absolute values.

User Pihentagy
by
5.2k points

2 Answers

2 votes

Use pythagoras theorem

d = √((x₁ - x₂)² + (y₁ - y₂)²)

d = √((-5 - 7)² + (3 - 3)²)

d = √((-12)² + 0)

d = √144

d = 12

User TuyenNTA
by
4.8k points
2 votes

Answer:

Explanation:

distance is √((x2-x1)^2+(y2-y1)^2)

so it will be √((12)^2+(0)^2)

or simply 12. since we are calculating distance, it is always going to be positive so technecally the formula is |√((x2-x1)^2+(y2-y1)^2)|

User Greatvovan
by
4.6k points